Новый вид рода Menacanthus Neumann (Mallophaga, Menoponidae) — паразит горного конька - Федоренко, И.А.; Харамбура, Я.И. (Вестник зоологии, 1980)
Two species of click beteles are described as new: Cardiophorus hiemalis sp. nov. distinct by long thin antennae, absence of a longitudinal process on the pronotum and a short first tarsal segment. Melanotus badchysicus sp. nov. differs from group M. humi-lis Schw. by a thin punctuation pronotum, antennal structure and male genitalia.